Exploring the Relationship Between Hospital Service Quality, Patient Trust, and Loyalty From a Service Encounter Perspective in Elderly With Chronic Diseases - Shie, An-Jin; Huang, Yung-Fu; Li, Guang-Yu; Lyu, Wen-Yi; Yang, Ming; Dai, You-Yu; Su, Zhao-Hui; Wu, Yenchun Jim (Frontiers in Public Health, 2022)
Based on the service encounter perspective, this study combines theoretical foundations for such factors as service quality and the characteristics of the hospital service industry to develop a research model scale to investigate whether the quality of hospital services affects patients’ perceptions of health service encounters, trust, and loyalty. Nowadays, with the advancement of medical technology, patients pay more attention to the quality of medical services and good service encounters provided by healthcare professionals in order to establish positive patient relationships; hospitals need to improve their own service quality and establish good patient trust relationships so that doctor-patient satisfaction and loyalty can be improved. In a review of related literature, this study found that most past studies focused on issues related of quality of medical services and patient satisfaction, but ignored those related to the relationship between medical service encounters and patient trust and loyalty, as well as the lack of scientific measurement markers for service encounters in the Chinese medical service industry. Therefore, this study uses the Service Encounter Perspective and Service Quality Theory Development Research Scale to collect and analyze data for a typical case of a Chinese tertiary hospital. Finally, this study explores the relationship between the four variables of service quality, service encounter, trust, and loyalty by means of a questionnaire and statistical analysis of the data. Finally, it is concluded that the higher the service quality of the hospital, the higher the customer trust, the higher the service encounter, and in the greater the doctor-patient loyalty.